Organic and mineral imprints in fossil photosynthetic mats of an East Antarctic lake. Issue 5 (12th July 2014) - Lepot, K.; Compère, P.; Gérard, E.; Namsaraev, Z.; Verleyen, E.; Tavernier, I.; Hodgson, D. A.; Vyverman, W.; Gilbert, B.; Wilmotte, A.; Javaux, E. J.
Abstract: Lacustrine microbial mats in Antarctic ice‐free oases are considered modern analogues of early microbial ecosystems as their primary production is generally dominated by cyanobacteria, the heterotrophic food chain typically truncated due to extreme environmental conditions, and they are geographically isolated. To better understand early fossilization and mineralization processes in this context, we studied the microstructure and chemistry of organo‐mineral associations in a suite of sediments 50–4530 cal. years old from a lake in Skarvsnes, Lützow Holm Bay, East Antarctica. First, we report an exceptional preservation of fossil autotrophs and their biomolecules on millennial timescales. The pigment scytonemin is preserved inside cyanobacterial sheaths. As non‐pigmented sheaths are also preserved, scytonemin likely played little role in the preservation of sheath polysaccharides, which have been cross‐linked by ether bonds. Coccoids preserved thylakoids and autofluorescence of pigments such as carotenoids. This exceptional preservation of autotrophs in the fossil mats argues for limited biodegradation during and after deposition. Moreover, cell‐shaped aggregates preserved sulfur‐rich nanoglobules, supporting fossilization of instable intracellular byproducts of chemotrophic or phototrophic S‐oxidizers. Second, we report a diversity of micro‐ to nanostructured CaCO3 precipitates intimately associated with extracellular polymeric substances, cyanobacteria, and/or other prokaryotes. Micro‐peloids Type 1 display features that distinguish them from known carbonates crystallized in inorganic conditions: (i) Type 1A are often filled with globular nanocarbonates and/or surrounded by a fibrous fringe, (ii) Type 1B are empty and display ovoid to wrinkled fringes of nanocrystallites that can be radially oriented (fibrous or triangular) or multilayered, and (iii) all show small‐size variations. Type 2 rounded carbonates 1–2 μm in diameter occurring inside autofluorescent spheres interpreted as coccoidal bacteria may represent fossils of intracellular calcification. These organo‐mineral associations support organically driven nanocarbonate crystallization and stabilization, hence providing potential markers for microbial calcification in ancient rocks.